Should elective neck dissection be routinely performed in patients undergoing salvage total laryngectomy?. Issue 3 (17th March 2014) - Pezier, T F; Nixon, I J; Scotton, W; Joshi, A; Guerrero-Urbano, T; Oakley, R; Jeannon, J-P; Simo, R
Abstract Background: The prevalence of occult neck metastasis in patients undergoing salvage total laryngectomy remains unclear, and there is controversy regarding whether elective neck dissection should routinely be performed. Method: A retrospective case note review of 32 consecutive patients undergoing salvage total laryngectomy in a tertiary centre was performed, in order to correlate pre-operative radiological staging with histopathological staging. Results: The median patient age was 61 years (range, 43–84 years). With regard to lymph node metastasis, 28 patients were pre-operatively clinically staged (following primary radiotherapy or chemoradiotherapy) as node-negative, 1 patient was staged as N1, two patients as N2c and one patient as N3. Fifty-two elective and seven therapeutic neck dissections were performed. Pathological analysis up-staged two patients from clinically node-negative (following primary radiotherapy or chemoradiotherapy) to pathologically node-positive (post-surgery). No clinically node-positive patients were down-staged. More than half of the patients suffered a post-operative fistula. Conclusion: Pre-operative neck staging had a negative predictive value of 96 per cent. Given the increased complications associated with neck dissection in the salvage setting, consideration should be given to conservative management of the neck in clinically node-negative patients (staged following primary radiotherapy or chemoradiotherapy).